A brief trip through chemistry, water, salt and oil: learn to speak and write as a chemist - García-Barradas, Oscar (Revista Eduscientia. Divulgación de la ciencia educativa, 2019)
Learning chemistry is perhaps not as complicated as it seems, or as we have made it seem. The atoms, the molecules and the way in which they are organized constitute the bricks with which everything is made. As in all areas of knowledge, it is necessary to assimilate the fundamental concepts that will allow us to understand and build our image of the universe, in this process, it is essential to acquire a scientific culture since we are children in which parents and teachers play a preponderant role.
Keywords: matter; atoms; bonds; molecules; chemistry